How cholesterol regulates endothelial biomechanics - Hong, Zhongkui; Staiculescu, Marius C.; Hampel, Paul; Levitan, Irena; Forgacs, Gabor (Frontiers in Physiology, 2012)
As endothelial cells form the barrier between blood flow and surrounding tissue, many of their functions depend on mechanical integrity, in particular that of the plasma membrane. As component and organizer of the plasma membrane, cholesterol is a regulator of cellular mechanical properties. Disruption of cholesterol balance leads to impairment of endothelial functions and eventually to disease. The mechanical properties of the membrane are strongly affected by the cytoskeleton. As Phosphatidylinositol-4,5-bisphosphate (PIP2) is a key mediator between the membrane and cytoskeleton, it also affects cellular biomechanical properties. Typically, PIP2 is concentrated in cholesterol-rich microdomains, such as caveolae and lipid rafts, which are particularly abundant in the endothelial plasma membrane. We investigated the connection between cholesterol and PIP2 by extracting membrane tethers from bovine aortic endothelial cells (BAEC) at different cholesterol levels and PIP2 conditions. We provide strong evidence that in endothelial cells the localization and metabolism of PIP2 is controlled by cholesterol. Our results suggest that in BAEC the role of PIP2, as a mediator of membrane-cytoskeleton adhesion, is regulated by cholesterol. Our findings confirm the specific role of cholesterol in endothelial cells and may have implications for cholesterol-dependent vascular pathologies.